Head and Neck Cancer Pain: Systematic Review of Prevalence and Associated Factors - Tatiana V. Macfarlane; Tanja Wirth; Sriyani Ranasinghe; Kim W. Ah-See; Nick Renny; David Hurman (Stilus Optimus, 2012)
Objectives: Pain is a major symptom in patients with cancer; however information on head and neck cancer related pain is limited. The aim of this review was to investigate the prevalence of pain and associated factors among patients with HNC. Material and Methods: The systematic review used search of MEDLINE, EMBASE and CINAHL databases to December 2011. Cancers of the oral mucosa, oropharynx, hypopharynx and larynx were included in this review with pain as main outcome. The review was restricted to full research reports of observational studies published in English. A checklist was used to assess the quality of selected studies. Results: There were 82 studies included in the review and most of them (84%) were conducted in the past ten years. Studies were relatively small, with a median of 80 patients (IQR 44, 154). The quality of reporting was variable. Most studies (77%) used self-administered quality of life questionnaires, where pain was a component of the overall scale. Only 33 studies reported pain prevalence in HNC patients (combined estimate from meta-analysis before (57%, 95% CI 43% - 70%) and after (42%, 95% CI 33% - 50%) treatment. Only 49 studies (60%) considered associated factors, mostly tumour- or treatment-related. Conclusions: The study has shown high levels of pain prevalence and some factors associated with higher levels of pain. There is a need for higher quality studies in a priority area for the care of patients with head and neck cancer.